Evaluation of the competitiveness of the region of Republic of Kazakhstan - Bencheva, N.A.; Yesmagulova, N.D.; Okutaeva, S.T. (BUKETOV BUSINESS REVIEW, 2017)
This article attempts to determine the level of competitiveness of the regions of the Republic of Kazakhstan, using existing approaches. The authors have defined the essence of the concept of the region's competitiveness. The article examines the existing methods of assessing the competitiveness of the regions. Also, the article shows the system of competitiveness indicators of the region, consisting of three blocks of indicators: economic potential, regional efficiency and competitive advantages. Using the Pattern method, the authors have calculated the integral index of the competitiveness of the regions of the Republic of Kazakhstan. The article categorizes the regions according to the level of competitiveness. According to the results of the study, the authors came to the conclusion that no region of the republic belongs to regions with a high level of competitiveness. Seventy percent of the regions have a low level of competitiveness in the region's economy. This study allows us to draw the following conclusion: the advantage of the Pattern method is that the list of indicators for assessing the competitiveness of the region can be changed depending on the specifics and specificity of individual regions, as well as on existing research goals and objectives. Using this method allows you to determine the competitive advantages of the regions, as well as their problems, which will be solved in the future.